PENGARUH KEPEMILIKAN PEMERINTAH, LEVERAGE, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Anwar, Resa Junita; Saryadi, Saryadi; purbawati, dinalestari (Jurnal Ilmu Administrasi Bisnis, 2018)
This study aimed to analyzed the influence of Government Ownership, Leverage, Profitability, and Corporate Growth on Dividend Policy. This study uses secondary data from the annual report by Indonesia stock exchange and Bloomberg platform, the population in this study include 21 state-owned enterprises listed in Indonesia Stock Exchange period of 2012-2016. Sample of this study consist of 13 state-owned enterprises that meet all the criteria. The analysis used is linear regression analysis with SPSS application program. Regression analysis showed that ,in partial, profitability has a significant positive effect on dividend policy. this study also found that Leverage and Growth of company have a significant negative effect to dividend policy. While Government ownership variable has no significant effect on dividend policy. As in simultaneous, Government Ownership, Leverage, Profitability and Corporate Growth show a significant effect on dividend policy.Â  Next, based on the results of multiple analysis, Government ownership is a variable that has a dominant influence on dividend policy. As analysis showed that value of beta coefficient (Î²) is -0.416, Leverage with a value of -0.398, and Corporate Growth -0.168.